2016
DOI: 10.1134/s0023158416020087
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of spiramycin removal from aqueous solution using heterogeneous photocatalysis

Abstract: International audienceSpiramycin macrolide antibiotic (SPM) can be photocatalytically degraded on TiO2 (anatase variety). The experiments are done in a batch reactor and the effect of some key parameters is investigated under low energy of artificial UV light. The reaction rate is affected by varying TiO2 dose, pH and SPM concentration. Under optimized conditions, a photodegradation efficiency of 98% is achieved and the SPM photodegradation follows pseudo-first order kinetics. The Langmuir–Hinshelwood (L–H) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 38 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…For a low catalyst concentration (i.e., 20 mg/L), only 43% of pollutant elimination was achived after 180 min of irradiation. A similar trend was noticed in previous literature studies in the case of other catalysts [51][52][53]. Such a behavior is specific for the photocatalytic systems, because the increase of catalyst content increases the number active sites available at the catalyst surface which determines the photons absorption and thus the photodegradation efficiency [54].…”
Section: Effects Of Some Operating Conditions On the Clofibric Acid Elimination With Zn4la400supporting
confidence: 86%
See 1 more Smart Citation
“…For a low catalyst concentration (i.e., 20 mg/L), only 43% of pollutant elimination was achived after 180 min of irradiation. A similar trend was noticed in previous literature studies in the case of other catalysts [51][52][53]. Such a behavior is specific for the photocatalytic systems, because the increase of catalyst content increases the number active sites available at the catalyst surface which determines the photons absorption and thus the photodegradation efficiency [54].…”
Section: Effects Of Some Operating Conditions On the Clofibric Acid Elimination With Zn4la400supporting
confidence: 86%
“…For a low catalyst concentration (i.e., 20 mg/L), only 43% of pollutant elimination was achived after 180 min of irradiation. A similar trend was noticed in previous literature studies in the case of other catalysts [51][52][53]. On the other hand, preliminary adsorption experiments were also conducted in dark under different conditions (mass of catalyst and pollutant) to assess the elimination of CA during this process and to determine the contact time necessary to achieve the adsorption-desorption equilibrium.…”
Section: Effects Of Some Operating Conditions On the Clofibric Acid Elimination With Zn4la400supporting
confidence: 60%
“…The maximum adsorption capacity of Cu 2+ (406.6 mg/g), Cd 2+ (436.7 mg/g), Zn 2+ (455.7 mg/g) and Ni 2+ (456.3 mg/g) [ 75 ]. Comparing chestnut shell pretreated with NaOH and pretreated with acid formaldehyde, the results showed that chestnut shell retreated with NaOH was more efficient in removing heavy metals [ 76 , 77 , 78 ]. Inyang et al [ 79 ] reviewed the biochar as a low-cost adsorbent for the removal of heavy metal removal; they found that the sorption mechanisms depends on different biochars and HMI contaminants.…”
Section: Chemical and Physical Methodsmentioning
confidence: 99%
“…The results of pollutant oxidation are then desorbed and dispersed from the semiconductor's surface. Moreover, in the use of wastewater and water, the oxidation process primarily aids in the destruction of various pharmaceutical chemicals [28][29][30][31].…”
Section: Oxidation Processesmentioning
confidence: 99%